Virtual Voting System - Gaurav Kumar; Smriti Gupta; Divya Agarwal; Astha Tiwari (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2021)
India's voting system plays an important role in Indian Democracy. The existing system is offline and has certain weaknesses. In recent years, the spread of covid19, inefficient rural voters, people far from their place of birth, paper waste affecting nature, budgets that should be used for development, invisible fraud, waste of human labor, have been recorded and can be avoided by the virtual voting system. The research aims to supply an easy and secure electoral system in India. The method used descriptive qualitative. The results indicate that a virtual voting system is environmentally friendly and is considered a resource-saving way for the election. It is because minimizes errors and increases voter participation through convenient virtual voting. In conclusion, a virtual voting system can develop anAadhar based advanced Electronic Voting Machine (EVM), which helps in a free and fair way of conducting elections